Material Effects on Tangent Modulus of Steel Square Hollow Section - Seyed Mohammad Reza Mortazavi; Milad Shakiba; Behrouz Zaeimdar (Journal of Rehabilitation in Civil Engineering)
The kind of mild steel, the Bauschinger effect because of strain reversal and strain ageing are indicated to affect significantly the tangent modulus of elasticity. Stub column specimens made from a material that has been pre-stretched in tension have a significantly lower tangent modulus of elasticity than those specimens made from as-received material; the reduction is caused by the Bauschinger effect and a resulting reduction in tangent modulus and yield strength. The reduction happens despite increases in material yield strength due to strain ageing after application of the tensile stretching. This paper has shown great reductions of tangent modulus of elasticity when specimens are made from material pre-stretched in tension compared with as-received specimens. Strain ageing has a great influence in minimizing the tangent modulus of elasticity reductions resulting from prior tensile prestretching. The initial tensile pre-strain of stress-relief-annealed specimens does not affect the tangent modulus of elasticity. No reduction was observed in the tangent modulus of elasticity of specimens prestrained in tension and stress-relief-annealed. The FE analysis according to the ABAQUS code was applied to simulate the stress-strain curves. The numerical and the experimental curves were reasonably similar to each other.